Proceedings of the Twenty-Fifth International Conference on Architectural Support for Programming Languages and Operating Syste 2020
DOI: 10.1145/3373376.3378462
|View full text |Cite
|
Sign up to set email alerts
|

Game of Threads

Abstract: As data sizes continue to grow at an unprecedented rate, machine learning training is being forced to adopt asynchronous algorithms to maintain performance and scalability. In asynchronous training, many threads share and update model parameters in a racy fashion to avoid costly interthread synchronization.This paper studies the security implications of these codes by introducing asynchronous poisoning attacks. Our attack influences training outcome-e.g., degrades model accuracy or biases the model towards an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…It also involves attackers encrypting sensitive or critical data. Previous research has demonstrated that model accuracy may be degraded by just compromising thread scheduling in a multi-threaded ML pipeline [42].…”
Section: Attacks Against Integritymentioning
confidence: 99%
“…It also involves attackers encrypting sensitive or critical data. Previous research has demonstrated that model accuracy may be degraded by just compromising thread scheduling in a multi-threaded ML pipeline [42].…”
Section: Attacks Against Integritymentioning
confidence: 99%
“…In Privman, developers need to separate their applications into a privilege server process and a main application process, in which the main application process only has limited privileges. Apart from software solutions, Intel introduced Software Guard Extensions (SGX) [14] to allow users to define private regions of memory for secured execution, which further inspired tons of security and privacy works [52,56]. However, none of these work explored integrating isolation and compartmentalization into the development flow of AR applications.…”
Section: Protecting Visual Datamentioning
confidence: 99%